Progressive Unilateral Proptosis and [18F]FDG-Avid Lesions Connoting Aggressive Disease in Radioiodine-Refractory Differentiated Thyroid Carcinoma - Edamadaka, Yeshwanth; Parghane, Rahul V.; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
Radioiodine-refractory differentiated thyroid carcinoma (RAIR-DTC) have poor prognosis as compared with radioiodine concentrating thyroid carcinoma. We present a case of follicular thyroid carcinoma presenting as a disseminated disease initially, underwent thyroid surgery and radioiodine (RAI) therapy. Following RAI, the patient developed a sudden-onset unilateral proptosis, finally diagnosed as orbital metastasis. [18F]-Fluorodeoxyglucose (FDG)-positron emission tomography-computed tomography identified FDG-avid metastatic lesions more numerous than the RAI-avid lesions. The patient was treated with local and systemic targeted therapy, but despite these treatments, he developed progressive disease indicating aggressive nature of the disease consistent with [18F]FDG-avid RAIR-DTC.
Keywords: radioiodine-refractory differentiated thyroid carcinoma (RAIR-DTC); radioactive iodine (RAI) therapy; [18F]FDG-PET/CT scan; orbital metastasis; targeted therapy